OPTIMIZING DIGITAL MARKETING FOR AVIATION SELECTION: A SYSTEMATIC REVIEW OF EMERGING TRENDS - Juliater Simarmata; Astri Rumondang Banjarnahor; Endang Hariningsih; Andre Yosafat; Gratia Atanka Barus (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The aviation industry has increasingly turned to digital marketing to stay competitive and meet evolving customer expectations. This study conducts a systematic literature review (SLR) to analyze emerging trends and best practices in digital marketing within the aviation sector. Utilizing articles from the Scopus database published between 2016 and 2023, the review identifies key strategies such as social media, search engine optimization (SEO), email campaigns, and the use of big data analytics. The findings highlight the effectiveness of these tools in enhancing customer engagement, satisfaction, and loyalty while addressing challenges such as high competition and data privacy concerns. This study underscores the need for a comprehensive understanding of digital marketing optimization to improve customer choice of airlines.